A photo-sensitizable phage for multidrug-resistant Acinetobacter baumannii therapy and biofilm ablation. Issue 3 (23rd November 2020) - Ran, Bei; Yuan, Yuyu; Xia, Wenxi; Li, Mingle; Yao, Qichao; Wang, Zuokai; Wang, Lili; Li, Xiaoyu; Xu, Yongping; Peng, Xiaojun
Abstract : APNB for multidrug-resistant A. Baumannii therapy and biofilms ablation. Abstract : Antibiotic abuse causes the emergence of bacterial resistance. Photodynamic antibacterial chemotherapy (PACT) has great potential to solve serious bacterial resistance, but it suffers from the inefficient generation of ROS and the lack of bacterial targeting ability. Herein, a unique cationic photosensitizer (NB) and bacteriophage (ABP)-based photodynamic antimicrobial agent (APNB) is developed for precise bacterial eradication and efficient biofilm ablation. Thanks to the structural modification of the NB photosensitizer with a sulfur atom, it displays excellent reactive oxygen species (ROS)-production ability. Moreover, specific binding to pathogenic microorganisms can be provided by bacteriophages. The developed APNB has multiple functions, including bacteria targeting, near-infrared fluorescence imaging and combination therapy (PACT and phage therapy). Both in vitro and in vivo experiments prove that APNB can efficiently treat A. baumannii infection. Particularly, the recovery from A. baumannii infection after APNB treatment is faster than that with ampicillin and polymyxin B in vivo . Furthermore, the strategy of combining bacteriophages and photosensitizers is employed to eradicate bacterial biofilms for the first time, and it shows the excellent biofilm ablation effect as expected. Thus, APNB has huge potential in fighting against multidrug-resistant bacteria and biofilm ablation in practice.